10.1111/acn.v9999.9999 (CrossRef Listing of Deleted DOIs, 2000)
Hypertrophic Cardiomyopathy (HCM) is one of the significant causes of heart failure. This study aimed to identify and validate potential therapeutic targets for HCM through bioinformatics analysis and in vitro and in vivo experiments. By analysing differentially expressed genes in HCM patients and combining multiple analytical approaches, key genes were screened. The functions of these genes were validated using AC16 cells under different mechanical force environments and Ang-II induction. HCM-like pathological cardiac remodelling mouse model was established to evaluate myocardial hypertrophy, fibrosis and cardiac remodelling. The results demonstrated that DUSP1 expression was downregulated in the myocardium of HCM patients. Mechanical force transduction activated the MAPK pathway and overexpression of DUSP1 suppressed ERK/MAPK activation and attenuated mechanotransduction-associated cardiomyocyte hypertrophy and hypertrophic gene expression. In vivo experiments showed that cardiac-specific restoration of DUSP1 expression alleviated pathological cardiac remodelling and fibrosis. This study suggests that DUSP1 functions as an endogenous regulator of mechanically activated MAPK signalling, thereby limiting pathological myocardial hypertrophy. These findings identify a previously underappreciated role of DUSP1 in linking mechanical stress-induced signalling with MAPK activation and pathological cardiac remodelling, suggesting DUSP1 restoration as a potential therapeutic strategy for HCM-like cardiac remodelling.